The Link of Abnormal Accrual Mispricing and Value- Glamour Stock Anomaly: Evidence from the Indonesian Capital Market - Erni Ekawati (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
The purpose of this study is to investigate whether abnormal accrual mispricing acknowledged in accounting literature is a manifestation of documented value-glamour anomaly in finance literature. This study proposes the traditional value-glamour proxies (sales growth, book-to-market, earningprice, cash flows-price, and size) and CFO/P ratio (ratio of operating cash flows and stock price) to explain the mispricing of abnormal accruals. Using a sample of 540 firm-year observations of companies listed on the Jakarta Stock Exchange (JSE) from the period of 1993 to 2003, the study finds that individually, only either the E/P or CFO/P ratio can pick up the mispricing attributed to abnormal accruals. These results can be interpreted as follows: (1) as captured by E/P ratio, abnormal accrual mispricing is due to the market’s inability to understand managers’ attempts to manage reported earnings; (2) as captured by the CFO/P, the market is unable to assess the persistence of cash flows. From a practical standpoint, this study has simplified the research agenda related to asset pricing. The result suggests that a researcher can control for the abnormal accrual mispricing and the value-glamour anomaly parsimoniously via just one variable, E/P ratio.Keywords: business performance; entrepreneurial orientation; environmental uncertainty